The human and the non-human: An accelerationist perspective on the generation of the project in the post-digital era (ARQUISUR Revista, 2020)
This paper aims to start a path of exploration on the generation of the project in the post-digital era through an accelerationist perspective. This implies the consideration of thematic intersections that link the cyborg, the trans, and the xeno. It also forges a vision of the project facing multiple possible futures, where robotics, machine learning, and digital manufacturing will be linked on multiple scales with the biotechnological and the post-natural. This will create an inexorable hybridization between the human and the non-human capable of redefining the inter-systemic relations built on the remains of the Anthropocene, heading towards a physical-digital convergence.
Keywords: accelerationism; postdigital; anthropocene; design; posthuman